2005
DOI: 10.1103/physrevlett.95.066101
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization of Gold Atoms on a Polar FeO(111) Surface

Abstract: The spatial distribution of single Au atoms on a thin FeO film has been investigated by low-temperature scanning tunneling microscopy and spectroscopy. The adatoms preferentially adsorb on distinct sites of the Moiré cell formed by the oxide layer and the Pt(111) support and arrange into a well-ordered hexagonal superlattice with 25 Å lattice constant. The self-organization is the consequence of an inhomogeneous surface potential within the FeO Moiré cell and substantial electrostatic repulsion between the ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
156
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(165 citation statements)
references
References 25 publications
8
156
0
1
Order By: Relevance
“…It would be interesting to investigate the orientational ordering and proton transfer dynamics of H 2 O in few-molecule clusters at lower temperatures, where such structures can be fully or partially frozen. One can further envision using the hydroxylated FeO film to control the bottomup synthesis of nanostructures based on hydrophilic components or precursors; though the templating effects of the bare FeO film itself are rather weak, being observed most clearly only at very low temperatures 23,24 , hydrogen bonding with surface OH groups should significantly enhance ordering, enabling directed selfassembly at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be interesting to investigate the orientational ordering and proton transfer dynamics of H 2 O in few-molecule clusters at lower temperatures, where such structures can be fully or partially frozen. One can further envision using the hydroxylated FeO film to control the bottomup synthesis of nanostructures based on hydrophilic components or precursors; though the templating effects of the bare FeO film itself are rather weak, being observed most clearly only at very low temperatures 23,24 , hydrogen bonding with surface OH groups should significantly enhance ordering, enabling directed selfassembly at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting modulation in the film's structure, best understood in terms of periodic variation in Fe-O buckling normal to the surface, creates an inhomogeneous adsorption potential 22 , so that adsorbed atoms and molecules have been found to form arrays with the periodicity of the film's superstructure instead of forming larger, more random aggregates 23,24 . Although previous temperature-programmed desorption (TPD), infrared reflection absorption spectroscopy and ultraviolet photoelectron spectroscopy studies of water adsorbed on ultra-thin FeO(111) films have shown rather weak interactions between water and the surface 12,25,26 , no microscopy studies have been reported to date and the potential effect of the films' moiré structure on the adsorption has not been considered.…”
mentioning
confidence: 99%
“…10 Among ultrathin oxide films, particular effort has been devoted to the investigation of single-layer oxides. 11 The interest in one-layer-thick oxides is manifold, in particular (i) two-dimensional oxides can be seen as model systems for the oxide/metal interface, allowing investigation by means of high-resolution scanning probe techniques; (ii) the vertical confinement and the elastic and electronic coupling with the metallic substrate allows stabilizing stoichiometries and atomic structures that can differ with respect to the corresponding bulk terminations, with important implications in chemical reactivity, 12,13 adsorption properties, 14 and magnetic ordering 15 of the resulting structures; and (iii) the wetting layer can represent the precursor phase for the growth of thicker films. 16,17 Single layers of transition metal oxides have been stabilized on noble and quasinoble metals such as, for instance, Pd, 18,19 Ag, 20,21 Pt, 22,23 Au, 24 and Ir.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] It has been pointed out that, due to non-uniform adsorption strength for ad-atoms within regions that present a different register with the substrate, the Moiré pattern provides a template for self-organization of gold atoms. 35 3 An additional reason of interest for this system is the magnetic nature of the oxide. At ambient pressure and low temperature, FeO assumes a distorted B1 structure.…”
Section: Introductionmentioning
confidence: 99%